1993
DOI: 10.1038/bjc.1993.320
|View full text |Cite
|
Sign up to set email alerts
|

Tumour localisation kinetics of photofrin and three synthetic porphyrinoids in an amelanotic melanoma of the hamster

Abstract: Summary In this study the localisation of porphyrinoid photosensitisers in tumours was investigated. To determine if tumour selectivity results from a preferential uptake or prolonged retention of photosensitisers, intravital fluorescence microscopy and chemical extraction were used. Amelanotic melanoma (A-Mel-3) were implanted in a skin fold chamber in Syrian Golden hamsters. Distribution of the porphyrin mixture Photofrin and three porphycenes, pure porphyrinoid model compounds, was studied quantitatively by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…* P < 0.01. c P < 0.001. b P < 0.0001. x P < 0.05. The presence of low Photofrin content in the skin and muscle of these patients is consistent with that found in other animal and clinical investigations (2,19,20). Muscle and skin Photofrin content in the present study, i.e., 0.71 F 0.63 and 1.20 F 0.62 ng/mg, respectively, are in general agreement with mean values of 2.24 ng/mg (range 0.69-3.86 ng/mg) in muscle and 2.19 ng/mg (range 0.67-3.16 ng/mg) in skin, reported in patients exposed to the same photosensitizing conditions as used in our trial (20).…”
Section: Discussionsupporting
confidence: 79%
“…* P < 0.01. c P < 0.001. b P < 0.0001. x P < 0.05. The presence of low Photofrin content in the skin and muscle of these patients is consistent with that found in other animal and clinical investigations (2,19,20). Muscle and skin Photofrin content in the present study, i.e., 0.71 F 0.63 and 1.20 F 0.62 ng/mg, respectively, are in general agreement with mean values of 2.24 ng/mg (range 0.69-3.86 ng/mg) in muscle and 2.19 ng/mg (range 0.67-3.16 ng/mg) in skin, reported in patients exposed to the same photosensitizing conditions as used in our trial (20).…”
Section: Discussionsupporting
confidence: 79%
“…39 In comparison, the molecular weight of our MNT is approximately 70 kDa, and that of low-density lipoprotein is about 3000 kDa. 40 Leunig et al, 41 who investigated tumor accumulation of different porphyrin-like photosensitizers, showed that the enhanced permeability and retention effect appears to be the most probable reason for the tumor selectivity of this type of photosensitizer. Therefore, qualitatively, free photosensitizer in tumor vessels and photosensitizer transported by MNT may be considered as similar in terms of enhanced permeability and retention effect, and perhaps even more favorable for the free photosensitizer.…”
Section: Discussionmentioning
confidence: 99%
“…chemical design and prediction of biological activity, only few QSAR studies on pharmacokinetics, subcellular localization, and tumor photosensitization of new PSs have been published [42, [227][228][229][230][231][232][233], and also very limited information about QSAR of porphycene PSs is available [234][235][236].…”
Section: Photobiological Activity In Vitromentioning
confidence: 99%
“…The tumor uptake of porphycenes is mainly related to their lipophilic character [234], non-ionic polar sidechains such as alkoxy-alkyl groups (ether-porphycenes) producing accelerated cell uptake of the corresponding derivarives [334,335]. The targeting efficiency and selectivity of several TPrPo and TMPo derivatives on the mouse MS-2 fibrosarcoma have been studied as a function of the type of substituents linked to the C9 position of the macrocycle by amide, ester or ether functional groups.…”
Section: Phototherapeutic Use Of Porphycenesmentioning
confidence: 99%